(untitled) (Research, Society and Development, 2020)
The present article aims to apply two conservation techniques (convective drying and lyophilization) to the jabuticaba peels and to characterize the powders obtained regarding the physicochemical parameters and bioactive compounds, thus evaluating their effect on their composition. Convective drying of the shells was performed in an air circulation oven at 50 °C and 1.0 m.s-1 air velocity for 24h, and lyophilization was performed at -50 °C for 48 h. In natura peels and powders obtained were characterized by the following physicochemical parameters: moisture, ash, lipids, protein, crude fiber, carbohydrates, water activity, pH, acidity, reducing sugars, total soluble solids; and bioactive compounds: anthocyanins, flavonoids, total phenolic compounds and antioxidant activity by ABTS. The use of jabuticaba bark in natura and after drying in flour form are viable for the development of new products, as a way to minimize the disposal of residues produced by the agrifood industry. Through the results obtained the jabuticaba bark flour was considered to be a source of phenolic compounds with antioxidant activity and fiber and could be considered a functional food. Comparing the drying techniques used, the lyophilization stood out because it presented a better preservation of the physicochemical parameters and the bioactive compounds.